2021
DOI: 10.1155/2021/8896210
|View full text |Cite
|
Sign up to set email alerts
|

Settlement Prediction of Foundation Pit Excavation Based on the GWO‐ELM Model considering Different States of Influence

Abstract: This paper proposes a novel grey wolf optimization-extreme learning machine model, namely, the GWO-ELM model, to train and predict the ground subsidence by combining the extreme learning machine with the grey wolf optimization algorithm. Taking an excavation project of a foundation pit of Kunming in China as an example, after analyzing the settlement monitoring data of cross sections JC55 and JC56, the representative monitoring sites JC55-2 and JC56-1 were selected as the training monitoring samples of the GWO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…This drawback can be resolved by integrating the ELM/KELM with an optimisation approach to achieve the optimal input weights and hidden layer biases that guarantee the best ELM/KELM performance ( 27 ). Therefore, one of the most popular improvements of the ELM is the Gray Wolf Optimization-Extreme Learning Machine (GWO-ELM), where the GWO is integrated into ELM in order to obtain the best input weights and biases ( 14 ). GWO was established by studying the hunting behavior of gray wolves ( 28 ).…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…This drawback can be resolved by integrating the ELM/KELM with an optimisation approach to achieve the optimal input weights and hidden layer biases that guarantee the best ELM/KELM performance ( 27 ). Therefore, one of the most popular improvements of the ELM is the Gray Wolf Optimization-Extreme Learning Machine (GWO-ELM), where the GWO is integrated into ELM in order to obtain the best input weights and biases ( 14 ). GWO was established by studying the hunting behavior of gray wolves ( 28 ).…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, the Principal Component Analysis (PCA) is considered one of the most recognized dimensionality reduction techniques ( 13 ), where it condenses most of the information in the database into a small dimensions' number. In addition, recently, the Gray Wolf Optimization-Extreme Learning Machine (GWO-ELM) has been considered one of the most popular ML algorithms ( 14 ). Therefore, the major aims of this study are as follows:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the use of particle swarm optimization was more effective and the PSO-ANFIS model was used to predict the ground settlement of the shield tunnel with good results. Qiao et al 15 proposed a combination prediction model called a grey wolf optimization algorithm and extreme learning machine (GWO-ELM) to predict ground subsidence caused by excavation pits in different influencing states. They found that the predicted results were good.…”
Section: Introductionmentioning
confidence: 99%
“…Shi-fan et al proposed a GWO-ELM model to enable training and prediction of ground subsidence. e optimized GWO-ELM model has significantly improved prediction ability and better prediction effect [5]. Zhan et al proposed an Elman network-based surface settlement prediction method to predict the surface settlement of deep foundation pits in oceanic lots and then correct the predicted values by the Markov chain model, thus further improving the accurate prediction of deep foundation pits in deep marine areas.…”
Section: Introductionmentioning
confidence: 99%